An Identification of The Understanding of Electrical Concept of Student Grade XII of Senior High School 2019/2020 in Central Aceh - Angga Fristian; Susanna Susanna; Ahmad Farhan (Asian Journal of Science Education, 2020)
This study aims to identify and differentiate the level of understanding of the electrical concepts of students' Grade XII Senior High Schools in Central Aceh. The population of this study was all students of Science students Grade XII Senior High Schools in Central Aceh which consisted of 19 senior high schools. The sample in this study were 115 students from six senior high schools in Central Aceh. The determination of the sample is done by purposive sampling. The approach which used is a qualitative approach with the type of descriptive research. Data collection techniques in this study used the test method. The form of the test instrument used is in the form of a three-tier test with a total of 12 items. The technique of data analysis was used in this study is percentage analysis. The percentage of the results shows there were 7.72% of students understood the concept, 51.52% of students lacked understanding of the concept, and 40.72% of misconceptions students. Thus, it can be concluded that the level of understanding of the electrical concepts of students senior high school in Central Aceh is at level 5 means very poor. As further recommendation for similar research it is best to not only identify the understanding of concepts, but also to overcome the lack of understanding of concepts and misconceptions in students so that students' understanding of concepts increases, especially in electrical concepts.